2022
DOI: 10.2196/31284
|View full text |Cite
|
Sign up to set email alerts
|

Online Patient Education Materials Related to Lipoprotein(a): Readability Assessment

Abstract: Background Lipoprotein(a) (Lp(a)) is a highly proatherogenic lipid fraction that is a clinically significant risk modifier. Patients wanting to learn more about Lp(a) are likely to use online patient educational materials (OPEMs). However, the readability of OPEMs may exceed the health literacy of the public. Objective This study aims to assess the readability of OPEMs related to Lp(a). We hypothesized that the readability of these online materials woul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Studies conducted over the past two decades clearly document health literacy-related deficits (e.g., exceedingly high reading demands, suboptimal layout design features) of a broad range of consumer health information. 8 , 9 , 10 , 11 , 12 To date, a handful of studies have critically assessed content and health literacy-related features of consumer COVID-19 information. In their assessment of COVID-19 consumer educational materials generated from Google, Yahoo!, and Bing internet searches (search terms included: coronavirus, COVID-19, COVID19, and COVID 19), Caballero et al found most to be difficult to read and lacked recommended features such inclusion of visual images and clearly defined manageable instructions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted over the past two decades clearly document health literacy-related deficits (e.g., exceedingly high reading demands, suboptimal layout design features) of a broad range of consumer health information. 8 , 9 , 10 , 11 , 12 To date, a handful of studies have critically assessed content and health literacy-related features of consumer COVID-19 information. In their assessment of COVID-19 consumer educational materials generated from Google, Yahoo!, and Bing internet searches (search terms included: coronavirus, COVID-19, COVID19, and COVID 19), Caballero et al found most to be difficult to read and lacked recommended features such inclusion of visual images and clearly defined manageable instructions.…”
Section: Introductionmentioning
confidence: 99%
“…As clinicians, we can engage in shared decision-making with our patients and utilize patient-focused educational materials to improve patients' knowledge of the risks associated with elevated Lp(a) and the importance of Lp(a) testing [ 54 ]. Patients can be directed to societies or advocacy groups, such as the Family Heart Foundation ( https://familyheart.org/ ), which offers frequent patient- and clinician-facing webinars on Lp(a), for more information, particularly with respect to family screening [ 55 ].…”
Section: Proposed Solutions To Common Barriers To Lp(a) Testingmentioning
confidence: 99%
“…Many web-based patient educational materials about cardiovascular disease (CVD) are inaccessible for the general public [ 1 ]. Artificial intelligence (AI) chatbots powered by large language models (LLMs) are a potential source of public-facing CVD information [ 2 - 4 ].…”
Section: Introductionmentioning
confidence: 99%